Defect‐Engineered Multi‐Intermetallic Heterostructures as Multisite Electrocatalysts for Efficient Water Splitting - Xiang‐Feng Wu; Zi‐Yan Li; Hui Wang; Jun‐Chuan Wang; Guo‐Qiang Xi; Xiao‐Jin Zhao; Chen‐Xu Zhang; Wu‐Gang Liao; Johnny C. Ho (Advanced Science)
Abstract Efficient water splitting for renewable hydrogen production requires the development of highly active and stable electrocatalysts. This study investigates the design and synthesis of defect‐engineered multimetallic heterostructures as advanced electrocatalysts for overall water splitting. A synergistic approach combining atomic‐scale defect engineering and multiphase heterostructures is employed to enhance catalytic activity. A series of highly porous intermetallic alloys (CoCuMoNi) with abundant defect sites are synthesized using a high‐temperature alloying‐dealloying technique. Due to the synergistic effect of multiphase interfaces, built‐in electric fields, and defect engineering, the CoCuMoNi catalyst exhibits excellent bifunctional activity for water splitting (Hydrogen evolution reaction: 14 mV@10 mA cm−2; Oxygen evolution reaction (OER): 211 mV@10 mA cm−2; Overall water splitting: 1.559 V@100 mA cm−2), with significantly enhanced activity compared to pure metals and conventional materials. Additionally, these structures demonstrate excellent stability and durability. Advanced characterization techniques and density functional theory (DFT) reveal that the formation of defect sites and heterojunctions not only induces electronic modulation but also enhances intermetallic interactions and charge transfer from Ni and Mo to Cu and Co, facilitating intermediate formation and transformation, thereby boosting intrinsic activity. This work highlights the potential of defect‐engineered multimetallic heterostructures as scalable and efficient electrocatalytic platforms, paving the way for their practical applications in clean energy technologies.